Forest fires and management efforts in Indonesia (a review). Issue 1 (May 2020) - Aminah; Krah, CY; Perdinan
Abstract: The area of Indonesia's forests has continues to shrink from year to year. The causes of this reduction have been mainly forest fires and the clearing of forest land into plantations and other nonagricultural uses. The area of Indonesia's forest consumed by fires in 2018 alone was about three times that of the previous year, 2017. These rising concern has pushed the Government into putting up divers efforts to control forest fires. This paper makes a general review of the forest fires in Indonesia, its impacts on humans and the natural resources with a special focus on water. The paper also discusses and brings out some possible loopholes in the system that might have contributed to the persistence of the forest fires. The major source of data for this review is secondary data from the ministry of environment and forestry, Indonesia, other sources were also considered for supporting data. This paper consists of 1. Introduction, 2. Causes of Forest and Land Fires in Indonesia, 3. Effects and impacts of Forest and Land Fires, 4. Water Footprint on Forest and Land Fires, 5. Fire Management Systems in Indonesia.